Low prevalence of collateral cerebral circulation in the circle of Willis in patients with severe carotid artery stenosis and recent ischemic stroke - Badacz, Rafał; Przewłocki, Tadeusz; Karch, Izabela; Pieniążek, Piotr; Rosławiecka, Agnieszka; Mleczko, Szymon; Brzychczy, Andrzej; Trystuła, Mariusz; Żmudka, Krzysztof; Kabłak-Ziembicka, Anna (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2015)
Introduction : The circle of Willis is thought to play a key role in development of collateral flow in patients with internal carotid artery stenosis (ICAS). Aim: To assess flow in the circle of Willis in patients with recent ischemic stroke (IS). Material and methods : The study included 371 patients, 102 symptomatic with severe ICAS and recent IS (within the last 3 months) (group I) and 269 asymptomatic with severe ICAS (group II). Flow in the middle (MCA), anterior (ACA) and posterior (PCA) cerebral arteries and pattern of the cross-flow through anterior (ACoA) and posterior (PCoA) communicating arteries were assessed with transcranial color-coded Doppler ultrasonography (TCCD). Results : The ACoA or PCoA was less prevalent in group I than in group II (54% vs. 78%, p < 0.001 and 20% vs. 42%, p < 0.001, respectively), resulting in lower peak-systolic velocity (PSV) in the MCA in group I vs. group II (p = 0.015). Any collateral pathway was present in 67% of patients in group I, compared to 86% in group II (p < 0.001). Both PSV and end-diastolic (EDV) flow velocity in the ACA were lower in patients with recent IS, compared to asymptomatic subjects (71 ±24 cm/s vs. 86 ±34 cm/s, p < 0.001 and 32 ±12 cm/s vs. 37 ±17 cm/s, p = 0.038, respectively). Presence of ACoA or PCoA and higher PSV in the MCA and ACA were associated with significant risk reduction of IS (RR = 0.28 (95% CI = 0.16–0.49, p < 0.001), RR = 0.28 (95% CI = 0.15–0.52, p < 0.001), RR = 0.97 (95% CI = 0.96–0.99, p < 0.001), RR = 0.99 (95% CI = 0.98–0.99, p < 0.032), respectively). However, ROC curves failed to show reliable MCA or ACA PSV cut-offs for IS risk assessment. Conclusions : The ACoA and PCoA seem to play a key role in the evaluation of IS risk in subjects with severe ICAS.